Widespread occurrence of the non‐pathogenic hare calicivirus (HaCV Lagovirus GII.2) in captive‐reared and free‐living wild hares in Europe. Issue 2 (14th July 2020) - Cavadini, Patrizia; Molinari, Stefano; Merzoni, Francesca; Vismarra, Alice; Posautz, Annika; Alzaga Gil, Vanesa; Chiari, Mario; Giannini, Francesca; Capucci, Lorenzo; Lavazza, Antonio
Abstract: The Lagovirus genus comprises both pathogenic viruses as European brown hare syndrome virus (EBHSV‐ GII.1) and rabbit hemorrhagic disease viruses (RHDV‐GI.1 and RHDV2‐GI.2), that principally infect European brown hares ( Lepus europeaus ) and European rabbits ( Oryctolagus cuniculus ), respectively, causing severe necrotic hepatitis, spleen enlargement and disseminated haemorrhage. This genus includes also non‐pathogenic agents, such as rabbit calicivirus (RCV‐E1 – GI.3) and the non‐pathogenic hare Lagovirus, provisionally named hare calicivirus (HaCV – GII.2). The latter had been identified for the first time in 2012 in the gut contents and faeces of healthy young hares raised in a breeding farm. In this study, we further investigated the presence of HaCV by testing the intestinal tract of 621 wild hares collected between 2010 and 2018 in Northern and Central Italy, and in 2011 in Austria, Germany and Spain. These wild hares were found dead for causes other than EBHS or were healthy hares shot during the hunting season. Forty‐three out of 322 hare samples from Italy and 14 out of 299 samples from Austria and Germany were positive for HaCV–GII.2 by RT‐PCR using universal primers for lagoviruses and primers specific for HaCV. Sequence analysis of the full capsid protein gene conducted on 12 strains representative of different years and locations indicated that these viruses belong to the same, single cluster as the prototype strain initially identified at the hares' farm (HaCV_Bs12_1). The relatively high level of genetic variation (88% nt identity) within this cluster suggests HaCVs may have been circulating widely in Europe for some time.